Aceturato de diminazeno lipossomal no tratamento da infecção por Trypanosoma evansi: testes in vitro e in vivo - Oliveira, Camila Belmonte (2014)
The aim of this study was to develop and to evaluate the therapeutic efficacy of liposomes diminazene aceturate and in vitro and by using mice experimentally infected with Trypanosoma evansi. In vitro tests were performed in culture medium at concentrations of 0.25, 0.5, 1, 2 and 3 mg/ml of diminazene aceturate convetional (CDMZ) and liposomal (L-DMZ). A total of 114 rats (Rattus norvegicus) were used of in vivo test. These rats were divided into 6 groups (A, B, C, D, E and F). Group A served as a negative control (uninfected and untreated). Rats in Group B served as a positive control and were infected with T. evansi. Animals in Group C were infected and treated with L-DMZ (single dose, 3.5 mg/kg-1), Group D was composed with infected and treated with C-DMZ animals (single dose, 3.5 mg/kg-1), Group E infected treated with L-DMZ animals for 5 consecutive days (3.5 mg/kg-1/dia) and Group F infected treated with C-DMZ animals for 5 consecutive days (3.5 mg/kg-1/dia). In vitro, a dose-dependent trypanocidal effect of L-DMZ was observed against the parasite. In vivo, the efficacy of L-DMZ and C-DMZ in different therapeutic protocols was similar. The analysis of biochemical and histological parameters on the 7th and 40th post-treatment revealed alterations in liver and kidney enzymes, and histological alterations in the structure of organs, especially in the animals treated with L-DMZ at 5 consecutive days. The results of this study showed that liposomal formulations may be a new alternative for the treatment of tripanosomoses, but future research could be undertaken to improve the conduction of liposomes and direction for greater efficiency.